2020
DOI: 10.1140/epjc/s10052-020-8399-3
|View full text |Cite
|
Sign up to set email alerts
|

A framework for hadronic rescattering in pp collisions

Abstract: In this article, a framework for hadronic rescattering in the general-purpose Pythia event generator is introduced. The starting point is the recently presented space–time picture of the hadronization process. It is now extended with a tracing of the subsequent motion of the primary hadrons, including both subsequent scattering processes among them and decays of them. The major new component is cross-section parameterizations for a range of possible hadron–hadron combinations, applicable from threshold energie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 84 publications
2
56
2
Order By: Relevance
“…Such an increase of the average p T with multiplicity has been observed by all experiments at LHC, being reasonably reproduced by Pythia (see, e.g., Ref. [64]) and leading to a gradual decrease ofσ ⊥ up to the rather high values of dN ch /dη. On the other hand, this effect is not properly described by QGSJET-II, in which case the decrease ofσ ⊥ is saturated already for relatively small values of dN ch /dη.…”
Section: Multiplicity Dependence Of Coalescence In Small Interacting Systemssupporting
confidence: 77%
“…Such an increase of the average p T with multiplicity has been observed by all experiments at LHC, being reasonably reproduced by Pythia (see, e.g., Ref. [64]) and leading to a gradual decrease ofσ ⊥ up to the rather high values of dN ch /dη. On the other hand, this effect is not properly described by QGSJET-II, in which case the decrease ofσ ⊥ is saturated already for relatively small values of dN ch /dη.…”
Section: Multiplicity Dependence Of Coalescence In Small Interacting Systemssupporting
confidence: 77%
“…[41]. A preliminary study in [34] showed that azimuthal anisotropies in the individual HH collision give unambiguous, but miniscule flow effects, and furthermore the many HH event planes of an AA collision point in random directions, further diluting any such effects. In the end, it is the asymmetries related to the AA geometry that matter for our studies.…”
Section: Multiparton Interaction Verticesmentioning
confidence: 98%
“…A related issue arises if the two programs represent event records differently, so that it might be impossible to trace the full particle history. A desire for convenience is one of the main motivations behind a recently developed framework for hadronic rescattering, implemented natively in Pythia [34]. This framework was inspired by UrQMD in the way it handles some of the processes and cross, sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, after the hadrons are fully formed we expect final state interactions between them. In this article we will not investigate final-state hadron interactions, although it is able to produce a sizable flow signal in PbPb collisions with Angantyr initial conditions [43], and has recently been implemented in PYTHIA8 [42]. As indicated by the discussion about the inherent ambiguity in defining a "hadronization time" in section 3, defining a transition between a string-dominated final state at early times, and a hadron dominated final state at late times, will require scrutiny.…”
Section: Jhep03(2021)270mentioning
confidence: 99%